2021
DOI: 10.7150/ijms.59267
|View full text |Cite
|
Sign up to set email alerts
|

The early surgical period in robotic radical hysterectomy is related to the recurrence after surgery in stage IB cervical cancer

Abstract: Objective: To identify the pattern of recurrence and assess the clinicopathologic prognostic factors for survival after robotic radical hysterectomy (RRH) in the treatment of stage IB cervical cancer. Methods: From December 2008 to March 2018, 64 cervical cancer patients who underwent RRH with pelvic lymph node dissection by a single surgeon were enrolled in this retrospective historical cohort timeline study. The patient's status was estimated in terms of operative outcomes, pathologic results, and survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Thus, our findings indicate a positive effect of surgical proficiency in MIS for early-stage cervical cancer. These results are in concordance with those of previously reported studies 15 - 18 , 22 .…”
Section: Discussionsupporting
confidence: 94%
“…Thus, our findings indicate a positive effect of surgical proficiency in MIS for early-stage cervical cancer. These results are in concordance with those of previously reported studies 15 - 18 , 22 .…”
Section: Discussionsupporting
confidence: 94%
“…Recently, several studies showed that surgical proficiency and surgical volume seem to play a substantial role in the oncologic outcomes of patients with early-stage cervical cancer treated with a surgical robot, with reported learning curves varying from 19 to 77 cases. [9][10][11][12] Analysing our own cohort retrospectively, we demonstrated a learning curve of at least 61 procedures during which the survival of patients was inferior to the experienced phase thereafter. 8 These nationwide and institutional studies all started their inclusions from the first robot-assisted procedures, soon after the robot was adopted for gynaecological purposes.…”
Section: Discussionmentioning
confidence: 95%
“…[4][5][6][7] Multiple studies on robot-assisted surgery for cervical cancer showed worse survival outcomes in early stages of the learning curve versus after mastery. [8][9][10][11][12] This learning curve effect could be one of the explanations for the results of recent retrospective and prospective studies reporting inferior survival of cervical cancer patients treated with minimally invasive surgery compared to open surgery. 13,14 These results underscored the need for structured and validated learning curricula intended to improve quality of care when introducing surgeons to a new technology, while minimizing learning curve effects and patient harm.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, there is a great debate about whether minimally invasive RH has poor survival outcome in patients with cervical cancer [25][26][27]. However, it is needed to evaluate whether the potential confounding factors, including surgeon's learning curve or intraoperative tumor spillage can influence on the oncologic outcome after minimally invasive RH [28][29][30]. In addition, a RCT will show the benefits and harms of RRH in cervical cancer separately from laparoscopic RH [31].…”
Section: Discussionmentioning
confidence: 99%